Mechanical and electrical response variation of the polyurethane–tin oxide–carbon nanotube composite microfiber depending on the chemical solution. Issue 4 (25th November 2018) - Cho, Hyuk‐Joon; Jeong, Sang‐Mi; Lim, Taekyung; Ju, Sanghyun
ABSTRACT: Toward the goal of smart sensor systems for wearable electronics, polymer microfiber‐based free‐standing sensors benefit from excellent flexibility, decent ductility, and easy wearability in comparison with thin‐film‐based sensing devices. Herein, we report a hydrophobic and conducting single‐strand microfiber‐based liquid‐phase chemical sensor consisting of polyurethane (PU), tin oxide (SnO2 ), and carbon nanotube (CNT) composites with applying a (1H, 1H, 2H, 2H‐heptadecafluorodec‐1‐yl) phosphonic acid (HDF‐PA)‐based self‐assembled monolayer. The free‐standing HDF‐PA‐treated PU–SnO2 –CNT composite microfiber showing selective filtering properties with the repellency of water and the penetration of an organic solvent is electrically and mechanically characterized. Finally, the single‐strand HDF‐PA‐treated PU–SnO2 –CNT composite microfiber‐based chemical sensor, which shows excellent mechanical properties and aqueous stability, is demonstrated to detect the presence of a chemical in pure water or counterfeit gasoline in pure gasoline by observing mechanical changes, especially variations in the length and diameter of the fiber, and monitoring the electrical resistance change. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 495–502 Abstract : The single‐strand 1H, 1H, 2H, 2H‐heptadecafluorodec‐1‐yl) phosphonic acid‐treated polyurethane–tin oxide–and carbon nanotube composite microfiber‐based chemical sensor can detect the presence of a chemical in pure water or counterfeit gasoline in pure gasoline by observing variations in the length and diameter of the fiber and monitoring the electrical resistance change.